The Crisis of the American Academic Workforce - Altbach, Philip; Finkelstein, Martin (International Higher Education, 2008)
Key to an improvement in so labor intensive an industry as higher education is its workforce: the professoriate. The American academic profession is, however, widely acknowledged to be in criticaland deterioratingcondition: demographic aging, remuneration, the high dropout rates in doctoral programs, lengthening time-to-degree, an increase of non-tenure track appointment. This change is having a profound, and largely unscrutinized, impact on American higher education.